Alternatives in blood operations when choosing non‐DEHP bags. Issue 2 (24th January 2017) - van der Meer, P. F.; Devine, D. V.; ,
Abstract : The use of di‐ethylhexyl‐phthalate (DEHP) in blood bags is under discussion due to toxicity concerns and possible restrictions. A questionnaire among 15 blood centres in nine countries showed that none so far have fully switched to non‐DEHP blood bags. If centres had to change, sites with a 42‐day outdate would choose for a shorter outdating period, while others would allow a higher haemolysis rate (but within current specifications). To improve red cell quality, about half of the centres are willing to move to an alternative red cell storage solution, while the other half would not change for various reasons.